Func tional treatment versus plaster for si mple el bow dislocations (FuncSiE): a randomized trial - Verleisdonk Egbert JMM (BMC Musculoskeletal Disorders, 2010)
Abstract Background Elbow dislocations can be classified as simple or complex. Simple dislocations are characterized by the absence of fractures, while complex dislocations are associated with fractures. After reduction of a simple dislocation, treatment options include immobilization in a static plaster for different periods of time or so-called functional treatment. Functional treatment is characterized by early active motion within the limits of pain with or without the use of a sling or hinged brace. Theoretically, functional treatment should prevent stiffness without introducing increased joint instability. The primary aim of this randomized controlled trial is to compare early functional treatment versus plaster immobilization following simple dislocations of the elbow. Methods/Design The design of the study will be a multicenter randomized controlled trial of 100 patients who have sustained a simple elbow dislocation. After reduction of the dislocation, patients are randomized between a pressure bandage for 5-7 days and early functional treatment or a plaster in 90 degrees flexion, neutral position for pro-supination for a period of three weeks. In the functional group, treatment is started with early active motion within the limits of pain. Function, pain, and radiographic recovery will be evaluated at regular intervals over the subsequent 12 months. The primary outcome measure is the Quick Disabilities of the Arm, Shoulder, and Hand score. The secondary outcome measures are the Mayo Elbow Performance Index, Oxford elbow score, pain level at both sides, range of motion of the elbow joint at both sides, rate of secondary interventions and complication rates in both groups (secondary dislocation, instability, relaxation), health-related quality of life (Short-Form 36 and EuroQol-5D), radiographic appearance of the elbow joint (degenerative changes and heterotopic ossifications), costs, and cost-effectiveness. Discussion The successful completion of this trial will provide evidence on the effectiveness of a functional treatment for the management of simple elbow dislocations. Trial Registration The trial is registered at the Netherlands Trial Register (NTR2025).